MODERN VIEWS ON ISCHEMIC KIDNEY DAMAGE IN NEWBORNS (World Bulletin of Public Health, 2022)
Ischemic nephropathy is one of the most severe and frequent kidney diseases in newborns in critical condition. The extreme manifestation of the disease is acute renal failure. However, clinical manifestations of ischemic nephropathy are masked by the critical condition of the child and are often diagnosed only with the maximum severity, while the outcome of the disease directly depends on the timeliness and adequacy of therapy [1, 2].
Keywords: directly; outcome; disease; depends